In-vitro Susceptibility Testing of Dermatophytes Isolated in Delhi (India) Against Five Antifungal Drugs - Datt, Shyama; Datt, Thakur; Singh, N.P (UNUSA Press, 2024)
Background: Over the past few decades, cases of dermatophytosis have been on the rise. Recently, the introduction of newer, less toxic antifungal drugs has improved treatment options. However, the prolonged use of antifungals has led to the emergence of acquired resistance among strains that were previously susceptible, as well as an increase in infections caused by less common species. This scenario underscores the growing need for rapid and accurate antifungal susceptibility testing methods. In this study, antifungal susceptibility was assessed using the in-vitro micro broth dilution method, adhering to the CLSI M38-A guidelines Methods: 60 clinical specimens were collected from Nail and skin of the patients of dermatophytosis from Delhi (India). Minimal inhibitory concentration (MIC) was performed in microtiter plates with U-bottom and incubated at 35° C. Reading were taken after 48 & 96 hrs of incubation for Trichophyton mentagrophytes and Trichophyton rubrum, against 5 antifungal drugs namely fluconazole, itraconazole (triazoles), griseofulvin, terbinafine and Luliconazole. Results: Most of the dermatophytes had uniform patterns of susceptibility to the antifungal agents tested. Low MIC values as 0.03μg/mL were found for 33.3%, 31.6% and 15% of isolates for itraconazole and terbinafine, respectively. Conclusion: In conclusion, it may be useful to undertake periodical screening programs to detect the antifungal susceptibility of newer antifungal agents.